Three sublayers in the SMAS: Observations of facial soft tissue using the stretched tissue dissection method focusing on the SMAS. Issue 1 (11th October 2022) - Watanabe, Koichi; Han, Aya; Inoue, Eiko; Iwanaga, Joe; Kikuchi, Keijiro; Haikata, Yuto; Nooma, Kunimitsu; Harano, Tatsuya; Tabira, Yoko; Saga, Tsuyoshi
Abstract: The characteristics of the superficial musculoaponeurotic system (SMAS), including the morphology of each part and the connection between tissues, remain controversial. The purpose of this study is to clarify the anatomy of the SMAS using our new dissection method. In this study, six hemi‐sides of heads from formalin‐preserved cadavers were used. Three were used for creating a horizontal section and three were used for creating the section along the axial line perpendicular to the surface of the skin, resulting in a gradual change from the coronal section at the lateral to the sagittal section at the median. The resected head was cut into slices with widths of 7 mm. The stretched tissue dissection method was performed by fixing a tissue slice to a board and pulling the skin outward to stretch the soft tissue. Blunt dissection was then performed under a microscope. The SMAS comprises three layers: superficial, intermediate, and deep. The superficial layer is a thin membrane directly connecting to the septa in the subcutaneous fat. The deep layer is the connective tissue in contact with the sub‐SMAS structure. The layer surrounded by the superficial and deep layer of the SMAS is the intermediate layer, containing connective tissue, adipose tissue, and facial muscles. The detailed findings of the SMAS obtained using this method resolve theoretical discrepancies and provide important insight for the field of facial surgery.